A COMPARATIVE STUDY ON THE FINANCIAL PERFORMANCE BETWEEN PUBLIC SECTOR AND PRIVATE SECTOR BANKS IN INDIA WITH SPECIAL REFERENCE TO SBI AND HDFC BANK - Priyajit Ray; Anuradha Priya Raha (RADJA PUBLIKA, 2023)
A lot depends on the financial institutions of an economy and their adequate performance drives the nation towards economic development. Banks are the main financial institutions of any country and they ensure financial stability by providing timely financial services to its customers. Both public and private sector banks are necessary in an economy which will give them a healthy competition among each other such that they will contribute towards the financial development of the country. The financial soundness of the banking sector is very much necessary especially in a country like India that will drive one step forward towards inclusive growth. Looking at the banking sector of our economy in the recent scenario, the researchers attempted to evaluate the financial performance of both public and private sector banks of our country with the help of the largest banks of their kind. CAMEL model was used in the study to compare the overall financial performance between the top most banks such that the objectives of the study can be fulfilled. The results of the study were quite clear and it ensures that the private sector banks of our country are giving tough competition to its peer counterparts. Finally, conclusion has been provided by the researchers based on the findings of the study such that the sector can be improved in coming times not only to satisfy its customers but also to ensure economic sustainability in the economy. Keywords: Banking Sector, CAMEL Model, Competition, Financial Institutions, Inclusive Growth. JEL Classification: C10, C65, C88, G21, Y10